Direction of the load on the elbow of the ball blocking handball goalie - EROL, BÜLENT; TİRYAKİ, ÇETİN (SPRINGER, 2008)
Elbow problems in goalkeepers in team handball handball goalie's elbow is common. The accepted mechanism in the common injuries is hyperextension of the elbow. The purpose of this study was to describe the elbow position at the time of impact of the ball on the hand. This study is based on video-analysis. Fifteen handball goalies (ten females and five males) who had been playing handball for a mean time of 6.5 years were used in the study. The participants were not aware of the details of the study. A national team member attacker performed repetitive shots toward the right side of each goalkeeper. The goalkeepers blocked the ball with their own usual style. Each block was videotaped with three digital cameras (one side view, one superior view, and one frontal view). The captured shots were later evaluated by three analysts as to the elbow position at the time of the impact. Seventy-eight out of 101 shots (77%) were valgus or mostly valgus load producing shots. The remaining 23 (23%) were hyperextension or mostly hyperextension load producing shots. This study shows that the elbows of the handball goalkeepers experience valgus loads at the time of ball blockade during the penalty shoot-out. A detailed understanding of the mechanism of the loads on the handball goalkeepers' elbow will help in defining ways to prevent and to treat handball goalie's elbow.
Keywords: handball goalkeeper; elbow; valgus load; hyperextension; injury mechanism; video analysis; TEAM HANDBALL; INJURIES; HYPEREXTENSION; GOALKEEPERS; JOINT